Mechanisms of tunneling nanotube-based propagation of neurodegenerative disease proteins - Lagalwar, Sarita (Frontiers in Molecular Neuroscience, 2022)
Tunneling nanotubes (TNTs), intercellular connections enriched with F-actin, were first identified as a viable means of cellular communication and organelle transport in animal cells at the early part of this century. Within the last 10 years, these microscopic and highly dynamic protrusions have been implicated in neurodegenerative disease propagation and pathogenesis. A host of aggregation-prone protein inclusions, including those containing alpha-synuclein, tau, prions and others, hijack this communication mechanism in both neurons and astrocytes. The exact cellular mechanisms underlying TNT-based propagation remain largely unknown, however, common practices can be identified. First, selective expression of the aggregation-prone form of proteins increases TNT density; next, endo-lysosomal pathways appear to support the loading and unloading of protein onto the TNT; and finally, TNT assembly results in the spontaneous formation of aggregation-prone protein inclusions in "acceptor" cells, indicating that TNTs are involved in not only the transport of inclusions but also in the seeding of new inclusions in naïve cells. These observations have implications for the spreading of neurodegenerative disease in the central nervous system and the consequent progression of symptoms. Here, I will summarize the empirical evidence of TNT-based aggregation-prone protein propagation to date, and propose an inclusive model of aggregate inclusion propagation along TNTs.